Bioactive Sesquiterpenoids from Santolina chamaecyparissus L. Flowers: Chemical Profiling and Antifungal Activity Against Neocosmospora Species - Eva Sánchez-Hernández; Jesús Martín-Gil; Vicente González-García; José Casanova-Gascón; Pablo Martín-Ramos (Plants)
Santolina chamaecyparissus L. (cotton-lavender) is receiving increasing attention due to its potential for modern medicine and is considered both a functional food and nutraceutical. In this work, the phytochemical profile of its flower hydromethanolic extract was investigated by gas chromatography–mass spectrometry, and its applications as a biorational for crop protection were explored against Neocosmospora spp., both in vitro and in planta. The phytochemical profiling analysis identified several terpene groups. Among sesquiterpenoids, which constituted the major fraction (50.4%), compounds featuring cedrane skeleton (8-cedren-13-ol), aromadendrene skeleton (such as (−)-spathulenol, ledol, alloaromadendrene oxide, epiglobulol, and alloaromadendrene), hydroazulene skeleton (ledene oxide, isoledene, and 1,2,3,3a,8,8a-hexahydro-2,2,8-trimethyl-,(3aα,8β,8aα)-5,6-azulenedimethanol), or copaane skeleton (cis-α-copaene-8-ol) were predominant. Additional sesquiterpenoids included longiborneol and longifolene. The monoterpenoid fraction (1.51%) was represented by eucalyptol, (+)-4-carene, endoborneol, and 7-norbornenol. In vitro tests against N. falciformis and N. keratoplastica, two emerging soil phytopathogens, resulted in effective concentration EC90 values of 984.4 and 728.6 μg·mL−1, respectively. A higher dose (3000 μg·mL−1) was nonetheless required to achieve full protection in the in planta tests conducted on zucchini (Cucurbita pepo L.) cv. ‘Diamant F1’ and tomato (Solanum lycopersicum L.) cv. ‘Optima F1’ plants inoculated with N. falciformis by root dipping. The reported data indicate an antimicrobial activity comparable to that of fosetyl-Al and higher than that of azoxystrobin conventional fungicides, thus making the flower extract a promising bioactive product for organic farming and expanding S. chamaecyparissus potential applications.